The Inﬂuence of Patellofemoral Degenerative Changes on the Outcome of the Unicompartmental Knee Replacement: A Prospective Study - Abdulkarim, Ali; Newton, Ayla C.; O'Donnell, Turlough; Neil, Michael J. (The Journal of Knee Surgery, 2020)
Unicompartmental knee arthroplasty (UKA) is a recognized procedure for treatment of medial compartment osteoarthritis. Patellofemoral (PF) joint degeneration is widely considered to be a contraindication to medial compartment UKA. We examined the validity of this preconception using information gathered prospectively on 147 consecutive patients who underwent the Repicci II UKA for medial compartment osteoarthritis between July 1999 and September 2000 by the same surgeon. The status of the PF joint was assessed intraoperatively in all patients, and accordingly patients were divided into two groups. Among them, 69 had associated PF osteoarthritis (group A), while 78 patients had a normal PF compartment (group B). Variables measured included the International Knee Society (IKS) score, limb alignment, and range of motion. Radiographs, demographic data, length of hospital stay, perioperative complications were also measured. All subsequent surgery and survivorship at 10 years were recorded. The mean follow-up was 9.4 years (range: 5–10.7 years) and results of the two groups were compared. We found no significant differences in terms of IKS scores, alignment, and flexion between the two groups. However, measured extension was significantly increased postoperatively in those patients with minimal or no PF joint degenerative disease (p < 0.05).
Keywords: patellofemoral; arthroplasty; unicompartmental; knee; arthritis